2013
DOI: 10.1186/2008-2231-21-8
|View full text |Cite
|
Sign up to set email alerts
|

Withholding or continuing beta-blocker treatment before dipyridamole myocardial perfusion imaging for the diagnosis of coronary artery disease? A randomized clinical trial

Abstract: BackgroundAlthough it has been shown that acute beta-blocker administration may reduce the presence or severity of myocardial perfusion defects with dipyridamole stress, little information is available about the potential effect of chronic beta-blocker treatment on the sensitivity of dipyridamole myocardial perfusion imaging (DMPI).MethodsAs a randomized clinical trial, one hundred twenty patients (103 male and 17 female) with angiographically confirmed CAD who were on long-term beta blocker therapy (≥3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition, during the maximal standard exercise test performed with suspended pharmacological therapy, CAD-G presented with a higher peak HR (approximately 7%) than CPX, in which the subjects were undergoing pharmacological therapy. Although these medications may have influenced our results, they are considered standard of care therapy for these patients 29 , 30 , and beta-blocker withdrawal can increase the risk of heart events 31 . Because VO 2 is present in the formula of CP and BP is present in the formula of CP and VP, it is important to consider that medications influenced peak VO 2 and peak systolic BP (as indicated by stepwise regression analysis), but did not influence CP and VP.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, during the maximal standard exercise test performed with suspended pharmacological therapy, CAD-G presented with a higher peak HR (approximately 7%) than CPX, in which the subjects were undergoing pharmacological therapy. Although these medications may have influenced our results, they are considered standard of care therapy for these patients 29 , 30 , and beta-blocker withdrawal can increase the risk of heart events 31 . Because VO 2 is present in the formula of CP and BP is present in the formula of CP and VP, it is important to consider that medications influenced peak VO 2 and peak systolic BP (as indicated by stepwise regression analysis), but did not influence CP and VP.…”
Section: Discussionmentioning
confidence: 95%
“…For example, the resting HR and HRR HV in advanced HF was reported higher in patients when beta-blockers were withheld during treadmill exercise than when the test was repeated in the same patients 3 hours after beta blocker administration 34 , while other studies have reported that in HF patients, the heart rate response to stress was not associated with beta blocker use 27 . The effects of withholding beta blockers before stress testing has previously been examined in myocardial imaging, and it was shown that beta blocker withdrawal did not affect the diagnostic sensitivity 35 . Yet, there is little knowledge about the relationship with beta blockers and hyperventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding a significant percentage of patients with history of smoking in the LMI group, we observed, during spirometric measurements, that these participants did not present changes in pulmonary function that could characterize an obstructive or restrictive lung disease; all of them presented FVC, FEV 1 , and FEV 1 / FVC normal values in relation to predicted values [20]. Regarding medications, it is important to emphasize that these are considered a standard therapy for these patients [41] given their use can contribute to improved prognosis [42]. us, the CAD and MI groups were under comparable medications, and only the CAD group did not present with an EFL at moderate intensity exercise.…”
Section: Discussionmentioning
confidence: 99%